MODIFIKASI STRUKTUR GEDUNG DENGAN BETON PRACETAK PADA APARTEMEN THE CONEXIO - Adita Devania; Andrias Rudi Hermawan (Politeknik Negeri Jakarta, 2020)
The Conexio Appartements in actual condition are designed using conventional reinforced concrete method and does not have good quality. While in the project also often afected by the weather. The use of precast concrete are having some excellence of them are not affected by the weather, well maintained quality, and earthquake resistant. The connection between the precast elements play an important role in precast buildings to make the buildings resistant to earthquake. This modification is intended to created earthquake resistant precast building according to SNI 2847:2013 with good quality control. In this study, the building will be modified into 8 floors precast building as planned and reviewed which will be analyzed by ETABS. From the results of the modification according to SNI 1726:2012 and SNI 2847:2013 we obtained, main beam dimension 40x60cm, secondary beam 35x55 cm, column dimension 65x65 cm, overtopping 6 cm for slab and using Splice sleeve grout for column to column connection, lap splices 500mm for beam-column connection, and 30x40cm for concrete consol dimension. Keywords : Precast, Splice Sleeve, Wet Connection.